2011
DOI: 10.2147/opth.s17350
|View full text |Cite
|
Sign up to set email alerts
|

Anterior segment changes following intravitreal bevacizumab injection for treatment of neovascular glaucoma

Abstract: Background:The purpose of this study was to describe anterior segment changes in a prospective, interventional, noncomparative case series of patients with neovascular glaucoma secondary to proliferative diabetic retinopathy treated with intravitreal bevacizumab.Methods:Five consecutive patients with neovascular glaucoma and a refractory, symptomatic elevation of intraocular pressure and pronounced anterior segment congestion received intravitreal bevacizumab 1.25 mg/0.05 mL. Follow-up examinations were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
(19 reference statements)
0
5
0
4
Order By: Relevance
“…14 At the same time as our observations, there have been case reports describing fibrovascular tissue contraction after the injection of bevacizumab, inducing angle closure and a consequent increase in IOP. 10,11 In a study of 5 cases of NVG treated with bevacizumab, our group 10 found regression of neovascularization and IOP control. However, 3 of these cases showed increased IOP 48 hours after injection, which required cycloablation for control.…”
Section: Discussionmentioning
confidence: 94%
“…14 At the same time as our observations, there have been case reports describing fibrovascular tissue contraction after the injection of bevacizumab, inducing angle closure and a consequent increase in IOP. 10,11 In a study of 5 cases of NVG treated with bevacizumab, our group 10 found regression of neovascularization and IOP control. However, 3 of these cases showed increased IOP 48 hours after injection, which required cycloablation for control.…”
Section: Discussionmentioning
confidence: 94%
“…İris neovaskülarizasyonu varlığında intravitreal bevacizumab enjeksiyonu sonrası açıdaki damarların hızla gerilemesi ile ilişkili olarak bazı hastalarda 1-2 gün içerisinde açının daralması hatta tamamen kapanması söz konusu olabilmektedir (7). İntravitreal enjeksiyon sonrası "akut" açı kapanması glokomu ise literatürde sadece bir gözde rapor edilmiştir (8).…”
Section: Discussionunclassified
“…Die in der Literatur beschriebenen IOD-Werte nach Zyklokryokoagulation lagen 1 Woche postoperativ bei 23,6 (± 11) mmHg und 1 Jahr postoperativ bei 8,2 (± 11,5) mmHg. Dies zeigte im Vergleich zu den präoperativen Werten (durchschnittlicher IOD präoperativ: 43,6 mmHg) eine signifikante Senkung [17,20]. Die Ergebnisse der Studie von Tzamalis et al (2011) zeigten eine signifikante IOD-Senkung von 46% 1 Jahr nach der Anwendung der Zyklophotokoagulation und von 54,1 % 1 Jahr nach der Behandlung mit Zyklokryokoagulation.…”
unclassified
“…Die intrakamerale oder intravitreale Anwendung von Bevacizumab führte jedoch zu einer schnellen Regression der Rubeosis iridis[18] und dadurch zu einer Drucksenkung. Die Langzeitauswirkungen auf die Regulation des IODs waren aber in diesen Studien nicht erfreulich[16][17][18]. Daher haben wir die intravitreale Anwendung von Bevacizumab mit der Zyklokryokoagulation kombiniert, um eine langfristige Druckregulierung zu erreichen.…”
unclassified